2018
DOI: 10.1039/c8md00278a
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and biological evaluation of benzimidazole–rhodanine conjugates as potent topoisomerase II inhibitors

Abstract: In this study, a series of benzimidazole-rhodanine conjugates were designed, synthesized and investigated for their topoisomerase II (Topo II) inhibitory and cytotoxic activities. The results from Topo II-mediated pBR322 DNA relaxation and cleavage assays showed that the synthesized compounds might act as Topo II catalytic inhibitors. Certain compounds displayed potent Topo II inhibition at 10 μM. The cytotoxic activities of these compounds against HeLa, A549, Raji, PC-3, MDA-MB-201, and HL-60 cancer cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Inhibitors of topoisomerases I and II (Topo I, II) are effectively used as anticancer agents. 45 The inhibitory properties of the promising anti-proliferative agents synthesized (29, 30 and 34-38) and those exhibited high safety prole against RPE1 (non-cancer cell line) relative to the tested cancer cell (27,(39)(40)(41)(42)(43)(44)(45)(46)(47), against human DNA topoisomerase IIa were investigated. Reports described the topoisomerase IIa inhibitory properties of 1,3-ylidene-4-piperidones encouraged these studies.…”
Section: Ppsa3 ¼mentioning
confidence: 99%
“…Inhibitors of topoisomerases I and II (Topo I, II) are effectively used as anticancer agents. 45 The inhibitory properties of the promising anti-proliferative agents synthesized (29, 30 and 34-38) and those exhibited high safety prole against RPE1 (non-cancer cell line) relative to the tested cancer cell (27,(39)(40)(41)(42)(43)(44)(45)(46)(47), against human DNA topoisomerase IIa were investigated. Reports described the topoisomerase IIa inhibitory properties of 1,3-ylidene-4-piperidones encouraged these studies.…”
Section: Ppsa3 ¼mentioning
confidence: 99%
“…This may be related to the fact that compounds with electron (15). Some new benzimidazole-rhodanine conjugates, 16 and 17, were designed, synthesized, and investigated for their cytotoxic activities against human cancer cell lines, including the human acute leukemia cell line (HL-60), the adenocarcinomic human alveolar basal epithelial cancer cell line (A549), the human lymphoma cancer cell line (Raji), and the human breast cancer cell line (MDA-MB-201) [35]. Compound 16, namely 5-[1-(4methylbenzyl)-1H-benzo[d]imidazol-2-yl]methylene-2-thioxothiazolidin-4-one, showed excellent inhibitory activity against tested cell lines, with IC 50 values of 2.66, 5.31, 4.48, and 6.42 µM, respectively, while the change of the 4-methyl substituent (compound 16) on the phenyl ring to 2-fluoro for compound 17 resulted in a loss of cytotoxic activity towards all cancer cell lines (Figure 7).…”
Section: -Substituted Rhodanine Derivativesmentioning
confidence: 99%
“…Compound 16, namely 5-[1-(4methylbenzyl)-1H-benzo[d]imidazol-2-yl]methylene-2-thioxothiazolidin-4-one, showed excellent inhibitory activity against tested cell lines, with IC 50 values of 2.66, 5.31, 4.48, and 6.42 µM, respectively, while the change of the 4-methyl substituent (compound 16) on the phenyl ring to 2-fluoro for compound 17 resulted in a loss of cytotoxic activity towards all cancer cell lines (Figure 7). This may be related to the fact that compounds with electron donating groups showed better Topo II inhibition than those with electron-withdrawing groups [35].…”
Section: -Substituted Rhodanine Derivativesmentioning
confidence: 99%
“…Studies have shown that the benzimidazole scaffold rings play a critical role in the antitumor activity [16,17]. In recent years, the modification of benzimidazole rings has and molecular docking studies have revealed that benzimidazole-containing derivatives act as Topo II catalytic inhibitors by blocking the adenosine triphosphate (ATP) binding site of the enzyme [16,18,20]. Chalcone derivatives have also been extensively investigated for their various physiological activities, such as anti-cancer, anti-oxidant, anti-inflammatory, anti-infective activities [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the modification of benzimidazole rings has become one of the hottest topics in the development of anti-cancer agents. Several benzimidazole derivatives have been reported as new Topo II inhibitors ( 1 , 2 and 3, Figure 1 ) [ 18 , 19 ]. Mechanistic and molecular docking studies have revealed that benzimidazole-containing derivatives act as Topo II catalytic inhibitors by blocking the adenosine triphosphate (ATP) binding site of the enzyme [ 16 , 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%